Evolution of Diversity in Metabolic Strategies - Ispolatov, y (eLife Sciences Publications Ltd, 2021)
Understanding the origin and maintenance of biodiversity is a fundamental problem. Many theoretical approaches have been investigating ecological interactions, such as competition, as potential drivers of diversification. Classical consumer-resource models predict that the number of coexisting species should not exceed the number of distinct resources, a phenomenon known as the competitive exclusion principle. It has recently been argued that including physiological tradeoffs in consumer-resource models can lead to violations of this principle and to ecological coexistence of very high numbers of species. Here we show that these results crucially depend on the functional form of the tradeoff. We investigate the evolutionary dynamics of resource use constrained by tradeoffs and show that if the tradeoffs are non-linear, the system either does not diversify, or diversifies into a number of coexisting species that does not exceed the number of resources. In particular, very high diversity can only be observed for linear tradeoffs. © 2021, eLife Sciences Publications Ltd. All rights reserved.